2010
DOI: 10.1007/s11069-010-9695-2
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphic features extraction from high-resolution topography: landslide crowns and bank erosion

Abstract: In recent years, new remote-sensed technologies, such as airborne and terrestrial laser scanner, have improved the detail and the quality of topographic information, providing topographical high-resolution and high-quality data over larger areas better than other technologies. A new generation of high-resolution (≤3 m) digital terrain models (DTMs) is now available for different areas and is widely used by researchers, offering new opportunities for the scientific community. These data call for the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
184
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(194 citation statements)
references
References 52 publications
7
184
2
1
Order By: Relevance
“…The minimum width value (3 cells) relies on the fact that sampling window needs to be centered on the cell of interest, thus the smallest area must comprise this cell and its eight nearest neighbors. Literature review (Pirotti and Tarolli, 2010;Tarolli et al, 2010) demonstrated that considering a window width range of 3-33 cells, quality of extracted features tends to a progressive worsening when windows are greater than ∼25 cells. We decided to apply the same kernel size range (3-33) to account also for a margin of uncertainty considering the different interpolation techniques of the study DTMs and different morphological characterization of the study cases.…”
Section: Minimum Curvaturementioning
confidence: 99%
“…The minimum width value (3 cells) relies on the fact that sampling window needs to be centered on the cell of interest, thus the smallest area must comprise this cell and its eight nearest neighbors. Literature review (Pirotti and Tarolli, 2010;Tarolli et al, 2010) demonstrated that considering a window width range of 3-33 cells, quality of extracted features tends to a progressive worsening when windows are greater than ∼25 cells. We decided to apply the same kernel size range (3-33) to account also for a margin of uncertainty considering the different interpolation techniques of the study DTMs and different morphological characterization of the study cases.…”
Section: Minimum Curvaturementioning
confidence: 99%
“…However, features were easily identified only when illuminated from the side, a shortcoming reported in many other studies (Štular 2011, Tarolli et al 2012, Tarolli 2014. Thus, road features were well defined on one aspect but difficult to distinguish on others.…”
Section: Discussionmentioning
confidence: 82%
“…This implies that landslide initiation zones have a lower planarity compared to other areas of consideration, which is based on two pre-defined conditions: (a) the boundary of landslide initiation zone delineated as a circle which ignores the real extent of the initiation zone and (b) the appropriate size of the moving window when the planarity is calculated. Tarolli et al (2012) introduced a logical assumption for determining the moving window size for the channel network recognition in order to reduce the noise and noted that a proper window size is the critical element for extract- ing appropriate geomorphological features. In our case, the moving window used in this study was 3 by 3, which is relatively optimal for 1 m LiDAR-derived DEM.…”
Section: Resultsmentioning
confidence: 99%